Conceptual data systems architecture principles for information systems - Jonsson, Tomas (Frontiers in Computer Science, 2023)
Information systems alignment with enterprises evolution, affects performance of enterprises. The systems conceptual and data quality, development time and sustainable life cycle management, are issues for enterprise competitiveness. The ability to directly generate enterprise information systems from models, has been thought of as a solution to improve on these issues. Model driven systems has been a research topic for decades. Fundamental principles for a proven model driven information systems architecture is outlined in this article. Architectural foundation is a separation of user communities conceptual domain from the information technical domain. The users domain is modelled as an information system model in three layers, conceptual data logic model, interface model and user community model. The technical domain is a platform, allowing modeling and execution of such a model. These principles have been applied in practice and proven viable. Two platforms and applications which adheres to these principles are briefly described.